PENGARUH FAKTOR HIGINE DAN PEMUAS PADA MOTIVASI DAN KINERJA: UJI TERHADAP TEORI HERZBERG - Pramono, Joko (Fakultas Ekonomi Universitas Islam 45, 2007)
Study about motivation is needed for HRM practices that able to motivated employees in work, but motivation theory is much variation so the kind of practices cannot choose precisely. This study tries to investigation Herzberg theory in government officer. The result is rejecting Herzberg theory, although employee?s motivation still has significant influence to performance. Advised for further research to take process theory of motivation if needed to investigation motivation theory especially in government officer